Linoleic acid stimulates neutral lipid accumulation in lipid droplets of maturing bovine oocytes - Carro, María De Las Mercedes; Buschiazzo, Jorgelina; Rios, Glenda Laura; Oresti, Gerardo Martin; Alberio, Ricardo (Elsevier, 2019)
Linoleic acid (LA) is a polyunsaturated fatty acid present in high concentrations in bovine follicular fluid; when added to maturation culture media, it affects oocyte competence (depending on the type and concentration of LA used). To date, little is known about the effective level of incorporation of LA and there is apparently no information regarding its esterification into various lipid fractions of the oocyte and its effect on neutral lipid storage. Therefore, the objective was to assess the uptake and subcellular lipid distribution of LA by analyzing incorporation of radiolabeled LA into oocyte polar and neutral lipid classes. The effects of various concentrations of LA on the nuclear status and cytoplasmic lipid content of bovine oocytes matured in vitro was also analyzed, with particular emphasis on intermediate concentrations of LA. Neutral lipids stored in lipid droplets were quantified with a fluorescence approach. Linoleic acid at 9 and 43 μM did not affect the nuclear status of oocytes matured in vitro, and 100 μM LA inhibited germinal vesicle breakdown, resulting in a higher percentage of oocytes arrested at the germinal state (43.5 vs. 3.0 in controls; P < 0.05). Bovine oocytes actively incorporated LA from the maturation medium (83.4 pmol LA per 100 oocytes at 22 hours of incubation; P < 0.05) and metabolized it mainly into major lipid classes, e.g., triacylglycerols and phospholipids (61.1% and 29.3%, respectively). Supplementation of the maturation medium with LA increased triacylglycerol accumulation in cytoplasmic lipid droplets at all concentrations assayed (P < 0.05). In conclusion, LA added to a defined maturation medium at concentrations that did not alter the nuclear status of bovine oocytes matured in vitro (9 and 43 μM) improved their quality by increasing the content of neutral lipids stored in lipid droplets. By directing the free fatty acid (LA) to triacylglycerol synthesis pathways and increasing the degree of unsaturation of membrane phospholipids, the oocyte was protected from lipotoxic effects (with an expectation of improved cryotolerance).